THE CURRENT STATUS OF LEAN MANUFACTURING IN SMALL, MEDIUM AND LARGE SCALE MANUFACTURING COMPANIES OF KARACHI, PAKISTAN - Wassan, Rano Khan; Chandio, Ghulam Sarwar; Yaseen Haider; Umair Sarwar; Ali Akbar; Muhammad Umair (Journal of Applied Engineering Science, 2022)
The major purpose of this study was to examine the current status of lean manufacturing in small, medium and large scale manufacturing companies situated in Karachi, Pakistan.The status of lean awareness, implementation, barriers and benefits in manufacturing companies were investigated through the questionnaire survey. The questionnaire was sent to 320 manufacturing companies and a response rate of 40.6% was received. SPSS 22.0 software was used to determine the average mean score for each factor and certain statistical analyses were performed to evaluate the results. It was observed that large organizations and SMEs both are fairly aware of the basic lean concepts but there is a sufficient difference in understanding of lean tools and techniques. Large organizations have a greater understanding and implementation of lean tools and techniques than SMEs. Some tools like 5S, Poka-yoke and TPM were found to have a similar status of implementation in various manufacturing companies irrespective of their size.The results of this study are applicable in Pakistani context, but could vary for other regions of the world, considering the awareness and challenges manufacturing enterprises are facing. To date there has been no research carried out in the context of large, small and medium manufacturing enterprises together in Pakistan, specifically in the Karachi region which investigate the status of lean awareness, implementation, benefits and barriers. Therefore, this study would serve as a foundation for conducting further in-depth studies on lean manufacturing in Pakistani manufacturing companies.
Keywords: lean manufacturing, lean awareness, lean barriers, lean implementation smes, large scale companies